Impact of the development of higher education on the architectural and planning features of ussr universities (1970-1980) - Popov, Aleksey; Semenchukova, Alexandra (Revista Conrado, 2023)
The study explores the period in the development of the architecture of Russian higher education institutions marked by a comprehensive approach and the mass implementation of cutting-edge solutions for that time. The main normative documents on the design of university campuses relevant to the period in question are studied. University master plans are examined and their similarities and differences are highlighted. A comparative analysis of the plans and current organization of university campuses is conducted based on specially selected criteria. Schemes with a color indication of the completed objects of the master plan are given for a visual illustration of the development of universities. The study describes common examples of the development of university complexes at the time of the USSR and identifies preconditions for the spatial development of universities. Despite the continued increase in the number of students, the general plans of many universities remain unimplemented and the architectural and planning potential of most institutes and universities is not realized to the fullest. In new projects for the development of these institutions, it is possible to use the initial general plans with adjustments to fit current trends and objectives. Keywords: Development of higher education institutions, USSR educational institutions, master plans of higher education institutions, USSR higher education system. RESUMEN El estudio explora el período en el desarrollo de la arquitectura de las instituciones de educación superior rusas marcado por un enfoque integral y la implementación masiva de soluciones de vanguardia para ese momento. Se estudian los principales documentos normativos sobre el diseño de campus universitarios relevantes para el período en cuestión. Se examinan los planes maestros universitarios y se destacan sus similitudes y diferencias. Se realiza un análisis comparativo de los planes y la organización actual de los campus universitarios a partir de criterios especialmente seleccionados. Se dan esquemas con una indicación de color de los objetos completados del plan maestro para una ilustración visual del desarrollo de las universidades. El estudio describe ejemplos comunes del desarrollo de complejos universitarios en la época de la URSS e identifica las condiciones previas para el desarrollo espacial de las universidades. A pesar del continuo aumento en el número de estudiantes, los planes generales de muchas universidades siguen sin implementarse y el potencial arquitectónico y de planificación de la mayoría de los institutos y universidades no se aprovecha al máximo. En nuevos proyectos para el desarrollo de estas instituciones, es posible utilizar los planes generales iniciales con ajustes para adaptarse a las tendencias y objetivos actuales. Palabras clave: Desarrollo de instituciones de educación superior, instituciones educativas de la URSS, planes maestros de instituciones de educación superior, sistema de educación superior de la URSS.